EDUCATIVE INNOVATION PROCESS IN UNIVERSITY FORMATION, NEW PRODUCTIVE BESTS PRACTICES IN EDUCATIVE TECHNOLOGY - Bartolomé Rubia-Avi; Rocío Anguita Martínez; Inés Ruíz Requies (Ediciones Universidad de Salamanca, 2010)
<!-- @page { margin: 0.79in } P { margin-bottom: 0.08in } --> The influence of educational innovation in the transformation of Spanish Universities to achieved the goals posed by the European Higher Education Area is a crucial aspect for this reform. This process of deep impact within the European countries is promoting the revision of traditional teaching methods. Small groups of teachers and communities of practice are leading this revision by reflecting upon the main issues affecting the higher education system at the same time that they propose horizontal innovations to overcome them. Information and Communication Technologies are becoming of special relevance with regard to the aforementioned innovations. This paper describes a experience conducted within the GSIC-EMIC research team that illustrates the efforts done by a community of teachers at the University of Valladolid (Spain) to analyze and improve their own teaching practices.